The level of religiosity and health behaviour of the elderly people. Pilot study - Babik, Kinga; Majda, Anna; Zalewska-Puchała, Joanna; Bodys-Cupak, Iwona (Nursing in the 21st Century, 2021)
THE LEVEL OF RELIGIOSITY AND HEALTH BEHAVIOUR OF THE ELDERLY PEOPLE. PILOT STUDY Introduction. Religiousness supports undertaking positive health behaviors.Aim. Showing the correlation between the level of religiosity and selected pro-health and risky behaviors among the elderly people.Material and methods. As research tools the original questionnaire and Scale of Individual Religion by A. Latała and P. Socha were used. The survey involved 120 participants. Analysis included 64 participants, who were all over 65 years old. U Mann-Whitney test, Kruskal-Wallis test, Spearman’s rank order correlation were used. The level of significance p